Phytochemical profiling of bioactive compounds in Telosma cordata (Tonkin jasmine) flower extract using GC-MS technique - Reme, S; Keisar, L D; Chitra, R; Ramalakshmi, A; Kumaresan, D; Manikanda, B N (Plant Science Today, 2025)
This study presents a comprehensive account of Telosma cordata and related species, focusing on taxonomy, distribution and distinguishing morphological traits. To elucidate the phytochemical landscape of the species, floral samples were subjected to Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The resulting chromatographic profiles revealed a diverse spectrum of primary and secondary metabolites, including volatile oils, phenolic compounds and bioactive flavonoids. The study identifies several major phytoconstituents with potential medicinal and nutritional relevance. The richness of antioxidant and antimicrobial metabolites in the methanolic extract suggests potential applications in developing natural therapeutic agents against oxidative stress and microbial infections. On the other hand, the hexane extract, dominated by heptadecanamine, indicates strong antimicrobial activity with possible use in pharmaceutical and industrial applications. Together, these findings emphasise the pharmacological potential of T. cordata flowers and justify further studies, including bioassays and formulation development.